Tape casting slurry, green porcelain tape and preparation method thereof

By preparing casting slurry containing specific components, the problem of casting difficulties in high-boron ceramic materials is solved, the fluidity and viscosity of the slurry are optimized, and high-quality raw ceramic tapes are prepared, which improves the overall performance of ceramic materials.

CN115991575BActive Publication Date: 2025-03-21LUOYANG ZHONGCHAO NEW MATERIAL SHARES CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202211230382.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-09-30
Publication Date
2025-03-21
Estimated Expiration
2042-09-30

AI Technical Summary

Technical Problem

In the prior art, casting of high-boron ceramic materials is difficult, mainly because the glass powder contains free boron compounds, resulting in poor slurry fluidity and poor quality of the raw ceramic belt.

Method used

By preparing a cast slurry containing calcium borosilicate glass powder, solvent, binder, plasticizer, dispersant, acrylic binder, alkane mixture, predispersant and additives, the interaction of these components is used to inhibit the influence of free boron compounds and improve the fluidity and viscosity of the slurry.

Benefits of technology

It is possible to prepare a slurry with moderate viscosity and fluidity, and obtain a green ceramic tape with uniform film thickness and flat surface, which improves the comprehensive performance of ceramic materials and is suitable for the application of low-temperature co-fired ceramic substrates.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115991575B_ABST
    Figure CN115991575B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of electronic ceramic substrate materials, and more specifically, to a tape casting slurry, a green porcelain tape and a preparation method thereof. The tape casting slurry of the present invention is made of component A, component B and component C, wherein component A comprises: calcium borosilicate glass powder; component B comprises: solvent, binder, plasticizer and dispersant; component C comprises: one or more of acrylic adhesive, alkane mixture, pre-dispersant and auxiliary agent; the mass ratio of component A, component B and component C is 100:(50-150):(0.02-20). The tape casting slurry provided by the present invention has moderate viscosity and good fluidity, and can obtain a green porcelain tape with uniform film thickness and smooth surface.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of electronic ceramic substrate materials, and more specifically to a tape-casting slurry, a green ceramic tape and a preparation method thereof. Background Art

[0002] With the rapid growth of demand for microwave / millimeter wave applications, especially the increasingly higher frequency of applications, materials are required to have low loss and stable dielectric constant within the application frequency range. LTCC materials have low conductor loss (gold and silver) and highly reliable dielectric layers, making them one of the best choices for microwave / millimeter wave components and packaging, and high-density system-level packaging.

[0003] Commercial DuPont951 glass is widely used. It is a composite system of lead borosilicate glass and ceramic Al2O3 filling phase. The material has high strength, but because the glass contains a large amount of heavy metal elements such as Pb and Ba, it is not environmentally friendly. Moreover, the material has a large loss value at high frequencies, which affects its use.

[0004] The CaO-SiO2-B2O3 glass-ceramic system has low dielectric loss and low and stable dielectric constant and is often used for LTCC substrates and packaging. In the pulping experiment stage, it was found that the powder was not easy to disperse and easy to agglomerate during tape casting. After optimizing the dispersion dosage, the slurry prepared still had poor fluidity and poor tape quality. Compared with other low-boron or boron-free ceramic powders, high-boron ceramics are more difficult to cast, mainly because the glass powder contains free boron compounds. B2O3 easily reacts with the hydroxyl groups in water, methanol, ethanol, PVA, and PVB to form a three-dimensional grid structure.

[0005] In the prior art, patent application CN114394768A chemically modifies the surface of glass powder, and the surface modifier is selected from at least one of silane coupling agent, titanate coupling agent, aluminate coupling agent, stearic acid and polyethylene glycol, and is mixed with water, anhydrous ethanol and acid-base regulator to form a surface modifier solution, which is mixed with calcium boron lanthanum glass powder and dried to obtain surface-modified calcium boron lanthanum powder. For example: 35g CaBLa modified glass powder + 45g (PMMA material 10% + ethyl acetate mixture, accounting for 28.66% by weight) + 55g Al2O3 powder is tape-casted. After the cut pieces are hot pressed and laminated, they are sintered according to the following curve: Rt (5℃ / min) → 250℃ / 30min (5℃ / min) → 480℃ / 30min (2℃ / min) → 875℃ / 60min. In this patent application, KH550, KH570, polyethylene glycol, modifier solution and modified CBLa powder are mainly used. The preparation process is cumbersome and the cycle is long. The final LTCC sintering temperature deviates from the standard process, and the loss is large. The commonly used CaO-SiO2-B2O3 microcrystalline glass contains a high boron content. High boron not only makes the sintering temperature of this type of glass difficult to control and the edge of the Ag conductor turns yellow, but most importantly, it thickens and gels the casting slurry, and the fluidity becomes poor. This makes casting difficult or obtains a raw porcelain tape with uneven film thickness and rough surface. Summary of the invention

[0006] In view of this, the purpose of the present invention is to provide a casting slurry, a green porcelain tape and a preparation method thereof. The present invention processes free boron compounds to prepare a slurry with moderate viscosity and good fluidity, and then prepares a green porcelain tape with uniform film thickness and smooth surface.

[0007] In order to achieve the above object, the present invention adopts the following technical solutions:

[0008] A casting slurry is made of component A, component B and component C, wherein:

[0009] Component A includes: calcium borosilicate glass powder;

[0010] Component B includes: solvent, binder, plasticizer, dispersant;

[0011] Component C includes: one or more of an acrylic adhesive, an alkane mixture, a pre-dispersant, and an additive;

[0012] The alkane mixture includes C15 to C35 alkanes;

[0013] The pre-dispersant includes one or more of organic ammonium salts, polyethers, polyolefins, and ester compounds;

[0014] The auxiliary agent includes a Group IVB metal acid ester coupling agent and / or a bimetallic coupling agent;

[0015] The mass ratio of component A, component B and component C is 100:(50-150):(0.02-20).

[0016] The present invention has no particular limitation on the source of the acrylic adhesive, which can be purchased from the market or prepared according to methods well known to those skilled in the art.

[0017] In the present invention, the alkane mixture includes C18 to C30 alkanes, and the alkane mixture is preferably paraffin;

[0018] The organic ammonium salt is a polyalkenoic acid ammonium salt, preferably a polyacrylic acid ammonium salt;

[0019] The polyether is polyethylene oxide;

[0020] The polyolefin is polyethylene wax;

[0021] The ester compound is one or more of triolein, triethyl phosphate, polyphosphate, and polyoxyethylene sorbitan monolaurate; the IVB group metal acid ester coupling agent is a zirconate coupling agent and / or a titanate coupling agent, and the titanate coupling agent is preferably a chelate titanate coupling agent and / or a coordination titanate coupling agent;

[0022] The bimetallic coupling agent is an aluminum-IVB group metal composite coupling agent, preferably an aluminum-titanium composite coupling agent and / or an aluminum-zirconium composite coupling agent.

[0023] In the present invention, the chelated titanate coupling agent is preferably ETDOP-212 (KR-212) produced by Kenrich Company, and its structure is

[0024]

[0025] KR-212 has good water resistance and is easily soluble in organic solvents, and can be directly used in solvent-based casting systems; the coordination titanate coupling agent is preferably KR-46 from Kenrich, and its structure is

[0026]

[0027] The chemical composition of KR-46 is di(dilaurylphosphite) tetraoctyloxytitanium. The titanium atom is converted from a tetravalent bond to a hexavalent bond, which reduces the reactivity of the titanate and improves water resistance. Therefore, the coordination titanate coupling agent has good water resistance, is soluble in organic solvents such as dibutyl phthalate, and can be directly used in solvent-based casting systems.

[0028] The acrylic adhesive used in the present invention can coat the powder, reduce the water absorption of the glass powder and the release of the boron compound, improve the dispersibility of the slurry, and thus improve the quality of the green tape;

[0029] Paraffin wax has a certain hydrophobicity and can modify the glass powder and inhibit the glass powder from absorbing water;

[0030] The coupling agents used in the present invention can be directly used as additives in an organic casting system, which is simple, easy to operate, has a short experimental cycle, and is more suitable for mass production and commercial applications. Among them, the aluminum-titanium composite coupling agent has the characteristics of both aluminate and titanate coupling agents, has a better coupling effect than traditional coupling agents, can greatly improve the compatibility of inorganic substances and polymers, reduce viscosity, and improve material processing performance and physical and mechanical properties.

[0031] In the present invention, the mass ratio of component A to acrylic adhesive is 100:(0.05-0.5), preferably 100:0.2;

[0032] The mass ratio of component A to C15-C35 alkane is 100:(0.05-0.5), preferably 100:0.1;

[0033] The mass ratio of component A to the pre-dispersant is 100:(0.02-0.2), preferably 100:(0.05-0.1);

[0034] The mass ratio of the component A to the auxiliary agent is 100:(0.1-1.2), preferably 100:(0.5-0.6).

[0035] In the present invention, the D50 particle size of the calcium borosilicate glass powder is 2.0 to 4.0 μm, preferably 2.1 to 2.5 μm.

[0036] In the present invention, the calcium borosilicate glass powder is made of components including the following raw materials:

[0037] CaCO3: 30-50 parts by weight;

[0038] SiO2: 20-35 parts by weight;

[0039] B2O3: 30-40 parts by weight;

[0040] P2O5: 0.8-2 parts by weight;

[0041] Li2CO3: 0.6-2 parts by weight;

[0042] K2CO3: 0.3-1.5 parts by weight;

[0043] Na2CO3: 0.1-1 parts by weight;

[0044] Fe2O3: 0.05-0.5 parts by weight;

[0045] ZrO2: 0.1-1 parts by weight;

[0046] MgO: 1.5-3 parts by weight;

[0047] Al2O3: 0.5-2.0 parts by weight;

[0048] CeO2: 0.2-2.0 parts by weight;

[0049] La2O3: 0.5~1.5 parts by weight.

[0050] The calcium borosilicate glass powder is preferably made of components including the following raw materials:

[0051] CaCO3: 36-41 parts by weight;

[0052] SiO2: 20-29 parts by weight;

[0053] B2O3: 31-37 parts by weight;

[0054] P2O5: 0.8-1.2 parts by weight;

[0055] Li2CO3: 0.6-1.2 parts by weight;

[0056] K2CO3: 0.3-0.9 parts by weight;

[0057] Na2CO3: 0.1-0.6 parts by weight;

[0058] Fe2O3: 0.05-0.2 parts by weight;

[0059] ZrO2: 0.1-0.5 parts by weight;

[0060] MgO: 1.5-2.8 parts by weight;

[0061] Al2O3: 0.8-2.0 parts by weight;

[0062] CeO2: 0.2-0.8 parts by weight;

[0063] La2O3: 0.5~0.9 parts by weight.

[0064] In the present invention, the purity of the raw material of the calcium borosilicate glass powder is ≥99%.

[0065] The preparation method of the calcium borosilicate glass powder comprises: mixing CaCO3, SiO2, B2O3, P2O5, Li2CO3, K2CO3, Na2CO3, Fe2O3, ZrO2, MgO, Al2O3, CeO2, La2O3 and ethanol and ball milling, drying, then heating and melting in a platinum crucible, and quenching with deionized water to obtain a high-boron LTCC glass frit; the preparation method specifically comprises: mixing CaCO3, SiO2, B2O3, P2O5 , Li2CO3, K2CO3, Na2CO3, Fe2O3, ZrO2, MgO, Al2O3, CeO2, La2O3 were mixed to obtain powder, ethanol was added to the powder in a ratio of ethanol to powder of 2:1, wet grinding was used to mix for 4 hours, the slurry was dried at 60°C, sieved with a 80-mesh screen, loaded into a platinum crucible, heated to 1200-1400°C and kept at this temperature for 1 hour, then poured into water to quench glass, and ball milled to obtain D 50 = 2.0 ~ 4.0 μm calcium borosilicate glass powder; the ethanol is preferably anhydrous ethanol, and the heating rate is 5 ° C / min.

[0066] In the present invention, the component B comprises:

[0067] 30 to 50 parts by weight of solvent;

[0068] 45-65 parts by weight of binder;

[0069] 2 to 8 parts by weight of plasticizer;

[0070] Dispersant 1 to 8 parts by weight.

[0071] The component B preferably comprises:

[0072] 32-45 parts by weight of solvent;

[0073] 45-62.5 parts by weight of binder;

[0074] 3 to 5 parts by weight of plasticizer;

[0075] Dispersant 2 to 3 parts by weight.

[0076] In the present invention, in component B, the solvent is ethanol and / or dimethyl carbonate;

[0077] The binder is polyvinyl butyral binder;

[0078] The dispersant is triethyl phosphate;

[0079] The plasticizer is diisodecyl phthalate.

[0080] The invention has no special restrictions on the sources of the solvent, binder, plasticizer and dispersant, which can be purchased on the market or prepared according to methods well known to those skilled in the art; the preparation method of the polyvinyl butyral binder comprises: dissolving 20wt% polyvinyl butyral in ethanol and dimethyl carbonate, and adding 0.02-0.2wt% triethyl phosphate to improve sedimentation; the mass ratio of anhydrous ethanol: dimethyl carbonate is preferably 1:1; the solvent is preferably a mixed solution of anhydrous ethanol and dimethyl carbonate in a mass ratio of 1:1.

[0081] The invention utilizes the addition of component C to eliminate the influence of the boron compound in the raw material on the fluidity of the subsequent slurry, and the viscosity of the prepared casting slurry is 900-1600 mpa.s.

[0082] The present invention also provides a method for preparing the above-mentioned casting slurry, comprising: mixing component A, component B, and component C to obtain the casting slurry; the mixing method is preferably ball milling; the ball milling time is 2 to 12 hours; after the mixing, the system is preferably vacuum degassed.

[0083] The method for preparing the above-mentioned casting slurry preferably includes: mixing component A with an acrylic adhesive, an alkane mixture, and a pre-dispersant, and then mixing with component B to obtain the casting slurry; or, mixing component A, component B and an auxiliary agent to obtain the casting slurry.

[0084] The present invention found in the pulping experiment stage that the powder is not easy to disperse and is easy to agglomerate during tape casting. Even if the dispersant dosage is optimized, the problem of poor fluidity of the prepared slurry and poor quality of the tape casting cannot be solved. Compared with other low-boron or boron-free porcelain powder casting, high-boron casting is more difficult, mainly because the glass powder contains free boron compounds. Boron compounds are not only easy to absorb water but also easy to react with the binder polyvinyl butyral (PVB) or polyvinyl alcohol (PVA) to form PVA-[B(OH)4] with a three-dimensional gel structure. - Compounds make the casting slurry thicken and gel, resulting in poor dispersion and poor fluidity. In order to inhibit the hindrance of free boron compounds to the fluidity of the slurry, improve the casting fluidity of the glass powder and prepare a green tape with better quality, the glass powder is pretreated or additives are added during the slurry making process to eliminate the influence of free boron compounds.

[0085] The present invention also provides a green porcelain tape, which is made by tape casting the above-mentioned tape casting slurry.

[0086] The preparation method of the above-mentioned green porcelain tape comprises: making the above-mentioned casting slurry into a casting film, drying it, and obtaining a green porcelain tape; the three heating temperature zones of the casting equipment are respectively set to 40-49°C, 50-57°C and 58-65°C, preferably set to 45°C, 55°C and 60°C.

[0087] The surface of the green porcelain tape of the present invention is flat and smooth, the film thickness is uniform, the film thickness error does not exceed 5μm, and the strength, toughness and other properties meet the product processing requirements. The film thickness is 120-150μm, the surface roughness Rz is 0.17-0.22μm, the elongation at break is 2.6-3%, and the tensile strength σ t is 3.6~3.9MPa, and the yield strength σ s It is 3.3~3.6MPa.

[0088] The preparation method of the above-mentioned raw porcelain tape specifically includes: preheating the casting equipment for 30 minutes, filtering the above-mentioned casting slurry and then drawing it into a material box, and applying it on a special base tape with a scraper with a certain thickness. The scraper height is controlled at 300-450μm, and the casting speed is 100-200mm / min. The cast blank is dried on the casting machine to obtain a raw porcelain tape.

[0089] The preparation method of the green porcelain tape of the present invention has simple process flow, high controllability and good repeatability; the prepared ceramics have good environmental compatibility and are suitable for large-scale production.

[0090] The components used to prepare the tape-casting slurry in the present invention are all environmentally friendly components. The present invention suppresses the reaction between free boron compounds in the glass powder and the PVB binder by adding component C, and optimizes the ratio of the preferred solvent, dispersant and plasticizer to obtain a slurry system with moderate viscosity and good fluidity, and finally prepares a low-dielectric, low-loss, high-boron CaO-SiO2-B2O3 glass tape-casting green porcelain tape with good structure and performance. The green porcelain tape has a uniform film thickness, a film thickness error of no more than 5 μm, and a smooth surface. The green porcelain tape can be sintered to be dense at 810° C. to 850° C. and kept warm for 5 to 15 minutes.

[0091] The ceramics prepared by the green ceramic tape of the present invention have lower dielectric constant, dielectric loss and higher mechanical strength. The dielectric constant ε r :5.1~8.0、dielectric loss tanδ<1.2×10 -3 , bending strength> 180MPa, meeting the application requirements of low-temperature co-fired ceramic substrates, and having excellent application prospects. The present invention has a positive effect on improving the comprehensive performance of low-temperature co-fired ceramic substrate materials and promoting the independent research and development and industrialization of low-temperature co-fired ceramic materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0092] Figure 1 is a film thickness test diagram of Example 1;

[0093] Figure 2 This is a comparative film thickness test diagram;

[0094] Figure 3 is the surface morphology of the LTCC green ceramic tape of Example 1;

[0095] Figure 4 This is the surface morphology of the LTCC green ceramic tape of the comparative example;

[0096] Figure 5 This is the surface morphology of the LTCC green ceramic tape of Example 1 after sintering at 810° C. for 5 minutes;

[0097] Figure 6 This is the surface morphology of the comparative LTCC raw ceramic tape after sintering at 830°C for 15 minutes. DETAILED DESCRIPTION

[0098] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solution of the present invention. It is particularly important to point out that all similar replacements and modifications are obvious to those skilled in the art and they all fall within the scope of protection of the present invention. The method of the present invention has been described through preferred embodiments, and relevant personnel can obviously modify or appropriately change and combine the method herein without departing from the content, spirit and scope of the present invention to implement and apply the technology of the present invention.

[0099] In order to further illustrate the present invention, the following examples are used to describe it in detail. The raw materials used in the following examples of the present invention are all commercially available products, among which the chelated 200 type titanate coupling agent ETDOP-212 (KR-212) is purchased from Kenrich Company. The molecular weight of the acrylic adhesive in the examples of the present invention is ≤180000, the glass transition temperature is ≤70°C, and the viscosity (6% dissolved in dimethyl carbonate: anhydrous ethanol, VT-06 viscosity tester) is 50-300mpa.s.

[0100] Example 1

[0101] (1) Preparation of calcium borosilicate glass powder

[0102] CaCO3, SiO2, B2O3, P2O5, Li2CO3, K2CO3, Na2CO3, Fe2O3, ZrO2, MgO, Al2O3, CeO2 and La2O3 with purity ≥99% are used as main raw materials. Raw material pretreatment: MgO is pre-calcined at 800℃ and kept warm for 4h, Na2CO3, K2CO3 and B2O3 are dried in a vacuum drying oven at 120℃ for 2h for use; the materials are weighed and mixed according to the following mass percentage ratio: CaCO3: 40.8%, SiO2: 20.6%, B2O3: 30.5%, P2O5: 0.8%, Li2CO3: 0.6%, K2CO3: 0.3%, Na2CO3: 0.1%, Fe2O3: 0.2%, ZrO2: 0.1%, MgO: 2.4%, Al2O3: 2.0%, CeO2: 0.8%, La2O3: 0.8%. Anhydrous ethanol was added to the powder in a ratio of 2:1 by mass, and the mixture was mixed by wet grinding for 4 h. The slurry was dried at 60°C, sieved with a 80-mesh sieve, placed in a platinum crucible, and heated from room temperature to 1400°C at a heating rate of 5°C / min and kept at this temperature for 1 h. Then, pure water was poured into the glass to quench it. After ball milling, calcium borosilicate glass powder CaCO3-SiO2-B2O3-P2O5-Li2CO3-K2CO3-Fe2O3-Na2CO3-ZrO2-MgO-Al2O3-CeO2-La2O3 with a D50 of 2.5 μm was obtained.

[0103] (2) Preparation of casting slurry

[0104] Pretreatment of calcium borosilicate glass powder: Add 5 wt% of a homemade acrylic adhesive to the calcium borosilicate glass powder prepared in step (1), accounting for 0.2 wt% of the calcium borosilicate glass powder, and mix the two evenly using a high-speed mixing device;

[0105] The weight percentage content of each component in the organic phase is: solvent 45.0wt%, binder 52.5wt%, plasticizer 4.0wt%, dispersant 2.5wt%. The binder is 20wt% polyvinyl butyral dissolved in anhydrous ethanol and dimethyl carbonate by stirring, and the obtained polyvinyl butyral liquid binder has an anhydrous ethanol: dimethyl carbonate ratio of 1:1, and 0.02wt% triethyl phosphate is added to improve sedimentation. The solvent is a 1:1 mixture of anhydrous ethanol and dimethyl carbonate, the dispersant is triethyl phosphate, and the plasticizer is diisodecyl phthalate;

[0106] Weigh 200g of pretreated calcium borosilicate glass powder, add 90g of solvent, 5g of dispersant, 105g of binder and 8g of plasticizer, mix and ball mill for 8h, and obtain low-dielectric, low-loss, high-boron glass LTCC environmentally friendly casting slurry after vacuum degassing. The viscosity is 1300mpa.s, the slurry has good fluidity, and there is no obvious sedimentation, stratification or agglomeration after the slurry is placed for 4h.

[0107] (3) Preparation of green porcelain tape

[0108] The casting equipment was turned on, and the temperatures of the three heating zones of the casting machine were set to 45°C, 55°C and 60°C respectively. After preheating for 30 minutes, the casting slurry was filtered and pumped into the material box. The scraper height was controlled at 450μm and the casting speed was 110mm / min. The cast green sheet was naturally dried on the casting machine, rolled up and placed to obtain the LTCC green porcelain tape. The green porcelain tape had a smooth surface, a film thickness of 139.5±5μm, a surface roughness of Rz=0.18μm, an elongation at break=2.80%, and a tensile strength σ t =3.89MPa, yield strength σ s =3.56MPa, the film thickness test of the green porcelain tape of this embodiment is as follows Figure 1 As shown in the scanning electron microscope Figure 3 As shown by Figure 1 It can be seen that by treating free boron, a green porcelain tape with uniform film thickness can be prepared.

[0109] (4) Preparation of ceramics

[0110] The green ceramic tape prepared in step (3) was laminated and engraved into φ16.10×5 mm cylinders and 3.5×4.8×42 mm strips using an engraving machine. The temperature was raised to 500°C at a heating rate of 1°C / min, and the binder was removed for 3 h. The temperature was then raised to 810°C at a heating rate of 5°C / min, and the temperature was kept for 5 min to complete sintering. The scanning electron microscope image after sintering is as follows: Figure 5 As shown, test performance: dielectric constant ε r =5.70, dielectric loss tanδ=0.56×10 -3 , flexural strengthσ=216.3MPa.

[0111] Example 2

[0112] (1) Preparation of calcium borosilicate glass powder

[0113] CaCO3, SiO2, B2O3, P2O5, Li2CO3, K2CO3, Na2CO3, Fe2O3, ZrO2, MgO, Al2O3, CeO2 and La2O3 with purity ≥99% are used as main raw materials. Raw material pretreatment: MgO is pre-calcined at 800℃ and kept warm for 4h, Na2CO3, K2CO3 and B2O3 are dried in a vacuum drying oven at 120℃ for 2h for use; the materials are weighed and mixed according to the following mass percentage ratio: CaCO3: 40.5%, SiO2: 20.8%, B2O3: 31.9%, P2O5: 0.8%, Li2CO3: 0.6%, K2CO3: 0.3%, Na2CO3: 0.1%, Fe2O3: 0.1%, ZrO2: 0.1%, MgO: 1.5%, Al2O3: 2.0%, CeO2: 0.5%, La2O3: 0.8%. Anhydrous ethanol was added to the powder in a ratio of 2:1 by mass, and the mixture was mixed by wet grinding for 4 h. The slurry was dried at 60 °C, sieved through a 80-mesh sieve, placed in a platinum crucible, and heated from room temperature to 1400 °C at a rate of 5 °C / min and kept warm for 1 h. Pure water was then poured into the mixture to quench the glass. Calcium borosilicate glass powder CaCO3-SiO2-B2O3-P2O5-Li2CO3-K2CO3-Fe2O3-Na2CO3-ZrO2-MgO-Al2O3-CeO2-La2O3 with a D50 of 2.5 μm was obtained by ball milling.

[0114] (2) Preparation of casting slurry

[0115] Pretreatment of calcium borosilicate glass powder: adding paraffin powder to the calcium borosilicate glass powder prepared in step (1), accounting for 0.1wt% of the calcium borosilicate glass powder, and mixing the two evenly with a high-speed mixing device;

[0116] The weight percentage content of each component in the organic phase is: solvent 42.0wt%, binder 50.0wt%, plasticizer 3.6wt%, dispersant 2.5wt%. The binder is 20wt% polyvinyl butyral dissolved in anhydrous ethanol and dimethyl carbonate by stirring, and the obtained polyvinyl butyral liquid binder has an anhydrous ethanol: dimethyl carbonate ratio of 1:1, and 0.05wt% triethyl phosphate is added to improve sedimentation. The solvent is a 1:1 mixture of anhydrous ethanol and dimethyl carbonate, the dispersant is triethyl phosphate, and the plasticizer is diisodecyl phthalate;

[0117] Weigh 200g of pretreated calcium borosilicate glass powder, add 84g of solvent, 5g of dispersant, 100g of binder and 7.2g of plasticizer, mix and ball mill for 8h, and obtain low dielectric, low loss, high boron glass LTCC casting slurry after vacuum degassing. The viscosity of the slurry is 952mpa.s, and the slurry has good fluidity. After 4h of storage, there is no obvious sedimentation, stratification or agglomeration.

[0118] (3) Preparation of green porcelain tape

[0119] The casting equipment was turned on, and the temperatures of the three heating zones of the casting machine were set to 45°C, 55°C and 60°C respectively. After preheating for 30 minutes, the casting slurry was filtered and pumped into the material box. The scraper height was controlled at 350μm and the casting speed was 130mm / min. The cast green sheet was naturally dried on the casting machine, rolled up and placed to obtain the LTCC green porcelain tape with a film thickness of 127.6±5μm, a surface roughness Rz=0.17μm, an elongation at break=2.63%, and a tensile strength σ t =3.62MPa, yield strength σ s =3.31MPa, the surface is flat and smooth, and the film thickness is uniform.

[0120] (4) Preparation of ceramics

[0121] The green porcelain tape prepared in step (3) was laminated and engraved into φ16.10×5mm cylinders and 3.6×4.9×45mm strips using an engraving machine. The temperature was raised to 500°C at a heating rate of 1°C / min, and the binder was removed for 3 hours. The temperature was then raised to 810°C at a heating rate of 5°C / min, and the temperature was kept for 5 minutes to complete the sintering. The performance was tested: ε r =5.91, tanδ=0.61×10 -3 , flexural strengthσ=208.6MPa.

[0122] Example 3

[0123] (1) Preparation of calcium borosilicate glass powder

[0124] CaCO3, SiO2, B2O3, P2O5, Li2CO3, K2CO3, Na2CO3, Fe2O3, ZrO2, MgO, Al2O3, CeO2 and La2O3 with purity ≥99% are used as main raw materials. Raw material pretreatment: MgO is pre-calcined at 800℃ and kept warm for 4h, Na2CO3, K2CO3 and B2O3 are dried in a vacuum drying oven at 120℃ for 2h for use; the materials are weighed and mixed according to the following mass percentage ratio: CaCO3: 38.6%, SiO2: 21.8%, B2O3: 32.8%, P2O5: 1.0%, Li2CO3: 0.6%, K2CO3: 0.3%, Na2CO3: 0.1%, Fe2O3: 0.1%, ZrO2: 0.1%, MgO: 1.5%, Al2O3: 1.8%, CeO2: 0.4%, La2O3: 0.9%. Anhydrous ethanol was added to the powder in a ratio of 2:1 by mass, and the mixture was mixed by wet grinding for 4 h. The slurry was dried at 60 °C, sieved through a 80-mesh sieve, placed in a platinum crucible, and heated from room temperature to 1300 °C at a heating rate of 5 °C / min and kept warm for 1 h. Then, the glass was poured into pure water to be quenched, and the calcium borosilicate glass powder CaCO3-SiO2-B2O3-P2O5-Li2CO3-K2CO3-Fe2O3-Na2CO3-ZrO2-MgO-Al2O3-CeO2-La2O3 with a D50 of 2.2 μm was obtained by ball milling.

[0125] (2) Preparation of casting slurry

[0126] Pretreatment of calcium borosilicate glass powder: adding polyethylene wax to the glass powder prepared in step (1) at a ratio of 0.05 wt% of the calcium borosilicate glass powder, and mixing the two evenly with a high-speed mixing device;

[0127] The weight percentage content of each component in the organic phase is: solvent 42.0wt%, binder 57.5wt%, plasticizer 4.2wt%, dispersant 2.5wt%. The binder is 20wt% polyvinyl butyral dissolved in anhydrous ethanol and dimethyl carbonate by stirring, and the obtained polyvinyl butyral liquid binder has an anhydrous ethanol: dimethyl carbonate ratio of 1:1, and 0.10wt% triethyl phosphate is added to improve sedimentation. The solvent is a 1:1 mixture of anhydrous ethanol and dimethyl carbonate, the dispersant is triethyl phosphate, and the plasticizer is diisodecyl phthalate;

[0128] Weigh 200g of pretreated calcium borosilicate glass powder, add 84g of solvent, 5g of dispersant, 115g of binder and 8.4g of plasticizer, mix and ball mill for 4h, and obtain low-dielectric, low-loss, high-boron glass LTCC casting slurry after vacuum degassing. The viscosity of the slurry is 1220mPa.s, and the slurry has good fluidity. After the slurry is placed for 4h, there is no obvious sedimentation, stratification or agglomeration.

[0129] (3) Preparation of green porcelain tape

[0130] The casting equipment was turned on, and the temperatures of the three heating zones of the casting machine were set to 45°C, 55°C and 60°C respectively. After preheating for 30 minutes, the casting slurry was filtered and pumped into the material box. The scraper height was controlled at 400 μm and the casting speed was 130 mm / min. The cast green sheet was naturally dried on the casting machine, rolled up and placed to obtain the LTCC green porcelain tape with a film thickness of 135.6±5 μm, a surface roughness of Rz=0.19 μm, an elongation at break=2.91%, and a tensile strength σ t =3.65MPa, yield strength σ s =3.36MPa, the surface is flat and smooth, and the film thickness is uniform;

[0131] (4) Preparation of ceramics

[0132] The green porcelain tape prepared in step (3) was laminated and engraved into φ16.10×5mm cylinders and 3.6×5.0×45mm strips using an engraving machine. The temperature was raised to 500°C at a heating rate of 1°C / min, and the binder was removed for 3 hours. The temperature was then raised to 830°C at a heating rate of 5°C / min, and the temperature was kept for 5 minutes to complete the sintering. The performance was tested: ε r =6.3, tanδ=0.70×10 -3 , flexural strengthσ=205.1MPa.

[0133] Example 4

[0134] (1) Preparation of calcium borosilicate glass powder

[0135] CaCO3, SiO2, B2O3, P2O5, Li2CO3, K2CO3, Na2CO3, Fe2O3, ZrO2, MgO, Al2O3, CeO2 and La2O3 with purity ≥99% are used as main raw materials. Raw material pretreatment: MgO is pre-calcined at 800℃ and kept warm for 4h, Na2CO3, K2CO3 and B2O3 are dried in a vacuum drying oven at 120℃ for 2h for use; the materials are weighed and mixed according to the following mass percentage ratio: CaCO3: 38.2%, SiO2: 21.8%, B2O3: 33.2%, P2O5: 0.8%, Li2CO3: 0.8%, K2CO3: 0.3%, Na2CO3: 0.2%, Fe2O3: 0.2%, ZrO2: 0.5%, MgO: 1.5%, Al2O3: 0.8%, CeO2: 0.8%, La2O3: 0.9%. Anhydrous ethanol was added to the powder in a ratio of 2:1 by mass, and the mixture was mixed by wet grinding for 4 h. The slurry was dried at 60°C, sieved through a 80-mesh sieve, placed in a platinum crucible, and heated from room temperature to 1300°C at a heating rate of 5°C / min and kept at this temperature for 1 h. Then, the glass was poured into pure water to be quenched, and the calcium borosilicate glass powder CaCO3-SiO2-B2O3-P2O5-Li2CO3-K2CO3-Fe2O3-Na2CO3-ZrO2-MgO-Al2O3-CeO2-La2O3 with a D50 of 2.2 μm was obtained by ball milling.

[0136] (2) Preparation of casting slurry

[0137] Pretreatment of calcium borosilicate glass powder: adding 0.1 wt% of triolein to the glass powder prepared in step (1) to pre-disperse the powder, and mixing the two evenly with a high-speed mixing device;

[0138] The weight percentage content of each component in the organic phase is: 40.0wt% solvent, 52.5wt% binder, 4.0wt% plasticizer, and 2.5wt% dispersant. The binder is a polyvinyl butyral liquid binder obtained by stirring and dissolving 20wt% polyvinyl butyral in anhydrous ethanol and dimethyl carbonate, wherein anhydrous ethanol: dimethyl carbonate = 1:1, and 0.15wt% triethyl phosphate is added to improve sedimentation. The solvent is a 1:1 mixture of anhydrous ethanol and dimethyl carbonate, the dispersant is triethyl phosphate, and the plasticizer is diisodecyl phthalate.

[0139] Weigh 200g of pretreated calcium borosilicate glass powder, add 80g of solvent, 5g of dispersant, 105g of binder and 8g of plasticizer, mix and ball mill for 4h, and obtain low-dielectric, low-loss, high-boron glass LTCC casting slurry after vacuum degassing. The viscosity of the slurry is 986mpa.s, and the slurry has good fluidity. After the slurry is placed for 4h, there is no obvious sedimentation, stratification or agglomeration.

[0140] (3) Preparation of green porcelain tape

[0141] The casting equipment was turned on, and the temperatures of the three heating zones of the casting machine were set to 45°C, 55°C and 60°C respectively. After preheating for 30 minutes, the casting slurry was filtered and pumped into the material box. The scraper height was controlled at 350μm and the casting speed was 100mm / min. The cast green sheet was naturally dried on the casting machine, rolled up and placed to obtain the LTCC green porcelain tape with a film thickness of 127.6±5μm, a surface roughness Rz=0.19μm, an elongation at break=2.65%, and a tensile strength σ t =3.68MPa, yield strength σ s =3.45MPa, the surface is flat and smooth, and the film thickness is uniform.

[0142] (4) Preparation of ceramics

[0143] The green porcelain tape prepared in step (3) was laminated and engraved into φ16.10×5 mm cylinders and 3.5×4.8×42 mm strips using an engraving machine. The temperature was raised to 500°C at a heating rate of 1°C / min, and the binder was removed for 3 h. The temperature was then raised to 830°C at a heating rate of 5°C / min, and the temperature was kept for 5 min to complete the sintering. The performance was tested: ε r =6.7, tanδ=0.75×10 -3 , flexural strengthσ=198.6MPa.

[0144] Example 5

[0145] (1) Preparation of calcium borosilicate glass powder

[0146] CaCO3, SiO2, B2O3, P2O5, Li2CO3, K2CO3, Na2CO3, Fe2O3, ZrO2, MgO, Al2O3, CeO2 and La2O3 with purity ≥99% are used as main raw materials. Raw material pretreatment: MgO is pre-calcined at 800℃ and kept warm for 4h, Na2CO3, K2CO3 and B2O3 are dried in a vacuum drying oven at 120℃ for 2h for use; the materials are weighed and mixed according to the following mass percentage ratio: CaCO3: 37.8%, SiO2: 21.6%, B2O3: 33.8%, P2O5: 0.8%, Li2CO3: 0.8%, K2CO3: 0.3%, Na2CO3: 0.2%, Fe2O3: 0.2%, ZrO2: 0.5%, MgO: 1.5%, Al2O3: 0.8%, CeO2: 0.8%, La2O3: 0.9%. Anhydrous ethanol was added to the powder in a ratio of 2:1 by mass and mixed for 4 h by wet grinding. The slurry was air-dried and then dried at 60 °C. It was sieved with a 80-mesh sieve and placed in a platinum crucible. The temperature was raised from room temperature to 1300 °C at a rate of 5 °C / min and kept at this temperature for 1 h. Then, pure water was poured into the quenched glass and the calcium borosilicate glass powder CaCO3-SiO2-B2O3-P2O5-Li2CO3-K2CO3-Fe2O3-Na2CO3-ZrO2-MgO-Al2O3-CeO2-La2O3 with a D50 of 2.2 μm was obtained by ball milling.

[0147] (2) Preparation of casting slurry

[0148] The weight percentage content of each component in the organic phase is: solvent 40.0wt%, binder 52.5wt%, plasticizer 4.0wt%, dispersant 2.5wt%.

[0149] The binder is a polyvinyl butyral liquid binder obtained by stirring and dissolving 20wt% polyvinyl butyral in anhydrous ethanol and dimethyl carbonate, wherein the ratio of anhydrous ethanol to dimethyl carbonate is 1:1, and 0.15wt% triethyl phosphate is added to improve sedimentation. The solvent is a 1:1 mixed solution of anhydrous ethanol and dimethyl carbonate, the dispersant is triethyl phosphate, and the plasticizer is diisodecyl phthalate.

[0150] Weigh 200g of the calcium borosilicate glass powder of step (1), add 1g of chelated 200-type titanate coupling agent, 80g of solvent, 5g of dispersant, 105g of binder and 8g of plasticizer, mix and ball mill for 4h at one time, and obtain low-dielectric and low-loss high-boron glass LTCC casting slurry after vacuum degassing. The viscosity of the slurry is 1020mpa.s, the slurry has good fluidity, and no obvious sedimentation, stratification or agglomeration occurs after the slurry is placed for 4h.

[0151] (3) Preparation of green porcelain tape

[0152] The casting equipment was turned on, and the temperatures of the three heating zones of the casting machine were set to 45°C, 55°C and 60°C respectively. After preheating for 30 minutes, the casting slurry was filtered and pumped into the material box. The scraper height was controlled at 350μm and the casting speed was 100mm / min. The cast green sheet was naturally dried on the casting machine, rolled up and placed to obtain the LTCC green porcelain tape with a film thickness of 127.6±5μm, a surface roughness of Rz=0.21μm, an elongation at break=2.96%, and a tensile strength σ t =3.71MPa, yield strength σ s =3.41MPa, the surface is flat and smooth, and the film thickness is uniform.

[0153] (4) Preparation of ceramics

[0154] The green porcelain tape prepared in step (3) was laminated and engraved into φ16.10×5 mm cylinders and 3.6×4.9×45 mm strips using an engraving machine. The temperature was raised to 500°C at a heating rate of 1°C / min, and the binder was removed for 3 h. The temperature was then raised to 830°C at a heating rate of 5°C / min, and the temperature was kept for 5 min to complete the sintering. The performance was tested: ε r =7.12, tanδ=0.81×10 -3 , flexural strengthσ=197.3MPa.

[0155] Example 6

[0156] (1) Preparation of calcium borosilicate glass powder

[0157] CaCO3, SiO2, B2O3, P2O5, Li2CO3, K2CO3, Na2CO3, Fe2O3, ZrO2, MgO, Al2O3, CeO2 and La2O3 with purity ≥99% are used as main raw materials. Raw material pretreatment: MgO is pre-calcined at 800℃ and kept warm for 4h, Na2CO3, K2CO3 and B2O3 are dried in a vacuum drying oven at 120℃ for 2h for use; the materials are weighed and mixed according to the following mass percentage ratio: CaCO3: 37.2%, SiO2: 21.2%, B2O3: 34.2%, P2O5: 0.9%, Li2CO3: 0.6%, K2CO3: 0.4%, Na2CO3: 0.3%, Fe2O3: 0.2%, ZrO2: 0.4%, MgO: 2.0%, Al2O3: 1.0%, CeO2: 0.8%, La2O3: 0.8%. Anhydrous ethanol was added to the powder in a ratio of 2:1 by mass, and the mixture was mixed by wet grinding for 4 h. The slurry was air-dried and then dried at 60°C, sieved with a 80-mesh sieve, placed in a platinum crucible, and the temperature was raised from room temperature to 1200°C at a rate of 5°C / min and kept at this temperature for 1 h. Then, pure water was poured into the quenched glass, and the calcium borosilicate glass powder CaCO3-SiO2-B2O3-P2O5-Li2CO3-K2CO3-Fe2O3-Na2CO3-Fe2O3-ZrO2-MgO-Al2O3-CeO2-La2O3 with a D50 of 2.1 μm was obtained by ball milling.

[0158] (2) Preparation of casting slurry

[0159] The weight percentage of each component in the organic phase is: solvent 45.0wt%, binder 52.5wt%, plasticizer 4.0wt%, dispersant 2.5wt%.

[0160] The binder is a polyvinyl butyral liquid binder obtained by stirring and dissolving 20wt% polyvinyl butyral in anhydrous ethanol and dimethyl carbonate, wherein the ratio of anhydrous ethanol to dimethyl carbonate is 1:1, and 0.12wt% triethyl phosphate is added to improve sedimentation. The solvent is a 1:1 mixture of anhydrous ethanol and dimethyl carbonate, the dispersant is triethyl phosphate, and the plasticizer is diisodecyl phthalate.

[0161] Weigh 200g of the calcium borosilicate glass powder of step (1), add 1.2g of zirconium aluminate composite coupling agent, 90g of solvent, 5g of dispersant, 105g of binder and 8g of plasticizer, mix and ball mill for 4h at one time, and obtain low dielectric, low loss, high boron glass LTCC casting slurry after vacuum degassing. The viscosity of the slurry is 1100mpa.s, the slurry has good fluidity, and no obvious sedimentation, stratification or agglomeration occurs after the slurry is placed for 4h.

[0162] (3) Preparation of green porcelain tape

[0163] The casting equipment was turned on, and the temperatures of the three heating zones of the casting machine were set to 45°C, 55°C and 60°C respectively. After preheating for 30 minutes, the casting slurry was filtered and pumped into the material box. The scraper height was controlled at 350μm and the casting speed was 100mm / min. The cast green sheet was naturally dried on the casting machine, rolled up and placed to obtain the LTCC green porcelain tape with a film thickness of 132.6±5μm, a surface roughness of Rz=0.22μm, an elongation at break=2.71%, and a tensile strength σ t =3.86MPa, yield strength σ s =3.53MPa, the surface is flat and smooth, and the film thickness is uniform.

[0164] (4) Preparation of ceramics

[0165] The green porcelain tape prepared in step (3) was laminated and engraved into φ16.10×5 mm cylinders and 3.5×4.8×42 mm strips using an engraving machine. The temperature was raised to 500°C at a heating rate of 1°C / min, and the binder was removed for 3 h. The temperature was then raised to 830°C at a heating rate of 5°C / min, and the temperature was kept for 5 min to complete the sintering. The performance was tested: ε r =7.81, tanδ=0.85×10 -3 , flexural strengthσ=192.3MPa.

[0166] Comparative Example

[0167] (1) Preparation of calcium borosilicate glass powder

[0168] CaCO3, SiO2, B2O3, P2O5, Li2CO3, K2CO3, Na2CO3, Fe2O3, ZrO2, MgO, Al2O3, CeO2 and La2O3 with purity ≥99% are used as main raw materials. Raw material pretreatment: MgO is pre-calcined at 800℃ and kept warm for 4h, Na2CO3, K2CO3 and B2O3 are dried in a vacuum drying oven at 120℃ for 2h for use; the materials are weighed and mixed according to the following mass percentage ratio: CaCO3: 39.2%, SiO2: 21.6%, B2O3: 32.4%, P2O5: 0.8%, Li2CO3: 0.6%, K2CO3: 0.3%, Na2CO3: 0.1%, Fe2O3: 0.1%, ZrO2: 0.1%, MgO: 1.5%, Al2O3: 2.0%, CeO2: 0.5%, La2O3: 0.8%. Anhydrous ethanol was added to the powder in a ratio of 2:1 by mass and mixed for 4 h by wet grinding. The slurry was air-dried and then dried at 60 °C. It was sieved through a 80-mesh sieve and placed in a platinum crucible. The temperature was raised from room temperature to 1350 °C at a rate of 5 °C / min and kept at this temperature for 1 h. Then, pure water was poured into the glass to quench it. Calcium borosilicate glass powder CaCO3-SiO2-B2O3-P2O5-Li2CO3-K2CO3-Fe2O3-Na2CO3-ZrO2-MgO-Al2O3-CeO2-La2O3 with a D50 of 2.4 μm was obtained by ball milling.

[0169] (2) Preparation of casting slurry

[0170] The weight percentage content of each component in the organic phase is: solvent 45.0wt%, binder 47.5wt%, plasticizer 4.5wt%, dispersant 4.5wt%. The binder is 20wt% polyvinyl butyral dissolved in anhydrous ethanol and dimethyl carbonate by stirring, and the obtained polyvinyl butyral liquid binder has an anhydrous ethanol: dimethyl carbonate ratio of 1:1, and 0.2wt% triethyl phosphate is added to improve sedimentation. The solvent is a 1:1 mixture of anhydrous ethanol and dimethyl carbonate, the dispersant is triethyl phosphate, and the plasticizer is diisodecyl phthalate.

[0171] Weigh 200 g of the calcium borosilicate glass powder of step (1), add 90 g of solvent, 9 g of dispersant, 95 g of binder and 9 g of plasticizer, mix and ball mill for 12 h, and obtain a casting slurry after vacuum degassing. The viscosity of the slurry is 1510 mPa.s, the fluidity is poor, and the slurry settles, delaminates and agglomerates after being placed for 0.5 h.

[0172] (3) Preparation of green porcelain tape

[0173] The casting equipment was turned on, and the temperatures of the three heating zones of the casting machine were set to 45°C, 55°C and 60°C respectively. After preheating for 30 minutes, the casting slurry was filtered and pumped into the material box. The scraper height was controlled at 400 μm and the casting speed was 150 mm / min. The cast green sheet was naturally dried on the casting machine, rolled up and placed to obtain a green porcelain tape with a film thickness of 142.2±15 μm, a surface roughness of Rz=0.36 μm, an elongation at break=5.12%, and a tensile strength σ t =2.01MPa, yield strength σ s =1.86MPa, the film thickness test of green porcelain tape is as follows Figure 2 As shown in the scanning electron microscope Figure 4 As shown, the surface of the raw porcelain tape is smooth but slightly rough, with obvious stripes and pinholes, and the thickness difference between the edge and the middle film is large, >15μm.

[0174] (4) Preparation of ceramics

[0175] The green ceramic tape prepared in step (3) was laminated and engraved into φ16.10×5 mm cylinders and 3.5×4.8×42 mm strips using an engraving machine. The temperature was raised to 500°C at a heating rate of 1°C / min, and the binder was removed for 3 h. The temperature was then raised to 830°C at a heating rate of 5°C / min, and the temperature was kept for 15 min to complete sintering. The scanning electron microscope image after sintering is as follows: Figure 6 As shown, test performance: dielectric constant ε r =5.86, dielectric loss tanδ=1.19×10 -3 , flexural strength σ=186.2MPa. The above description of the disclosed embodiments enables those skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but will conform to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A tape casting slurry, characterized in that: It is made of component A, component B, and component C, wherein component A is calcium borosilicate glass powder; the calcium borosilicate glass powder is made of the following raw materials: CaCO3: 30-41 parts by weight; SiO2: 20-35 parts by weight; B2O3: 30-40 parts by weight; P2O5: 0.8-2 parts by weight; Li2CO3: 0.6-2 parts by weight; K2CO3: 0.3-1.5 parts by weight; Na2CO3: 0.1~1 parts by weight; Fe2O3: 0.05~0.5 parts by weight; ZrO2: 0.1~1 parts by weight; MgO: 1.5-3 parts by weight; Al2O3: 0.5-2.0 parts by weight; CeO2: 0.2~2.0 parts by weight; La2O3: 0.5~1.5 parts by weight; Component B consists of solvent, binder, plasticizer and dispersant; The dispersant is triethyl phosphate; in component B, the solvent is ethanol and dimethyl carbonate; the binder is polyvinyl butyral binder; Component C is composed of one or more of an acrylic adhesive, an alkane mixture, a pre-dispersant, and an additive; The alkane mixture is paraffin; The pre-dispersant is one or more of organic ammonium salts, polyethers, polyolefins, and ester compounds; The ester compound is one or more of triolein, polyphosphate, and polyoxyethylene sorbitan monolaurate; The auxiliary agent is a Group IVB metal acid ester coupling agent and / or a bimetallic coupling agent; The mass ratio of component A, component B and component C is 100:(50~150):(0.02~20).

2. The tape casting slurry according to claim 1, characterized in that: The organic ammonium salt is a polyalkenoic acid ammonium salt; The Group IVB metal ester coupling agent is a zirconate coupling agent and / or a titanate coupling agent; The bimetallic coupling agent is an aluminum-IVB group metal composite coupling agent.

3. The tape casting slurry according to claim 2, characterized in that: The polyalkenoic acid ammonium salt is polyacrylic acid ammonium salt; The polyether is polyethylene oxide; The polyolefin is polyethylene wax; The titanate coupling agent is a chelate titanate coupling agent and / or a coordination titanate coupling agent; The aluminum-IVB group metal composite coupling agent is an aluminum-titanium composite coupling agent and / or an aluminum-zirconium composite coupling agent.

4. The tape casting slurry according to claim 1 or 2, characterized in that: The mass ratio of component A to acrylic adhesive is 100:(0.05~0.5); The mass ratio of component A to pre-dispersant is 100:(0.02~0.2); The mass ratio of component A to the auxiliary agent is 100:(0.1~1.2).

5. The tape casting slurry according to claim 1, characterized in that: The D50 particle size of the calcium borosilicate glass powder is 2.0-4.0 μm.

6. The tape casting slurry according to claim 1, characterized in that: The content of each component of component B is: 30-50 parts by weight of solvent; 45-65 parts by weight of binder; 2 to 8 parts by weight of plasticizer; Dispersant 1~8 parts by weight.

7. The tape casting slurry according to claim 1 or 6, characterized in that: The plasticizer is diisodecyl phthalate.

8. The method for preparing the tape casting slurry according to any one of claims 1 to 7, characterized in that: include: Component A, component B and component C are mixed to obtain a casting slurry.

9. A green porcelain tape, characterized in that: The film is made by tape casting of the tape casting slurry according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Modified calcium-boron-lanthanum glass powder, green tape, dielectric constant controllable LTCC substrate, packaging material and preparation method thereof

    CN114394768A

  • Reinforced calcium borosilicate microcrystalline glass composite material and preparation method thereof

    CN110683769A

  • Low-dielectric LTCC green tape as well as preparation method and use thereof

    CN110790568A

  • Alumina ceramic slurry as well as preparation method and application thereof

    CN114292091A